Clinical Consultation in the Workplace: Are There Implications for Response Attitudes? - Bárbara Gonzalez; Rosa F. Novo; Maria João Afonso; Matilde Fernandes; Ana Vieira (Psychologica Belgica)
The clinical-organizational context (where clinical psychology services are provided in the individuals’ professional setting) has still been insufficiently approached in research, namely the influence it may have on the response attitudes of individuals undergoing psychological assessment. Our main goal is to find out if, when psychological assessment occurs in the workplace context, patients being assessed present specific response bias that may have implications for the clinical results and correlative decisions. Five hundred and ten adult participants grouped in two samples of ambulatory patients – Clinical-Organizational Sample (COS n = 238) and Clinical Sample (CS n = 272) – were assessed with the Minnesota Multiphasic Personality Inventory-2-RF validity and substantive scales. Under-reporting is five times more frequent in the COS, which presents Defensiveness (11%), and Desirability (5%). In the CS, under-reporting is residual and over-reporting is more prevalent than in the COS. Clinical record information of COS participants presenting under vs. over-reporting also reveal differences concerning their circumstances, and type of clinical conditions. Comparing participants with under-reporting in each sample, the COS had lower clinical profiles, and tended to present excessively low psychopathology and symptomology values, suggesting higher defensiveness. Finally, the fact that 33% of the COS present biased response attitudes (i.e., 15% presented under-reporting and 18% presented over-reporting) has implications for both clinical and career decision making processes. In conclusion, there are relevant differences in response attitude and psychopathology features between outpatients assessed in a traditional clinical setting and in a clinical-organizational one, suggesting the professional context of the patients may influence motivations to disclosure psychological symptoms and problems.